Embracing the 2013 Curriculum: A Qualitative Metasummary of Problems - Dairabi Kamil (Indonesian Research Journal in Education |IRJE|, 2021)
This study seeks to synthesize research findings on problems in implementing the 2013 Curriculum in schools across the country. The terminal objective of this study is to construct a large picture of the issue across different contexts of the synthesized studies. Drawing on Qualitative Metasummary variant of the Qualitative Metasynthesis Method, data were collected through online searching of relevant research reports available in several databases. Data analyses followed the procedure suggested by Sandelowski and Barroso (2007) on 81 research reports. Findings of this study show that problems in the implementation of the 2013 curriculum can be grouped under ten topical categories, namely 1) teacher’s readiness; 2) assessment; 3) learning resources; 4) infrastructure; 5) introduction and training; 6) learning process; 7) time allocation; 8) student’s readiness; 9) regulation; and 10) monitoring and supervision. It was also found that 4 out of the 7 anticipated problems in the pre-implementation public assessment period of the curriculum exist in the synthesis.  It is therefore suggested that: 1) Continuous monitoring and assistance by related authorities of the implementation of the 2013 Curriculum is needed to help teachers and schools deal with the identified problems; 2) as teachers’ readiness seems to be the central problem in the implementation, solving this problem also help ease the other problems; 3) as the current study only on focuses the problems in the implementation of the curriculum, it does not necessarily mean that the curriculum is void of advantages and strength. Therefore, the researcher recommends research that looks into this side; and 4) as most of the anticipated problems existed in the synthesis, there seems to be so far inadequate control and follow-up of the valuable anticipation. Therefore, in the future, close attention and immediate actions should be taken to address such issues.